2012
DOI: 10.1038/onc.2012.402
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KRAS-induced epiregulin overexpression contributes to aggressive phenotype and is a promising therapeutic target in non-small-cell lung cancer

Abstract: KRAS mutations are one of the most common driver mutations in non-small-cell lung cancer (NSCLC) and finding druggable target molecules to inhibit oncogenic KRAS signaling is a significant challenge in NSCLC therapy. We recently identified epiregulin (EREG) as one of several putative transcriptional targets of oncogenic KRAS signaling in both KRAS-mutant NSCLC cells and immortalized bronchial epithelial cells expressing ectopic mutant KRAS. In the current study, we found that EREG is overexpressed in NSCLCs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 44 publications
2
71
2
1
Order By: Relevance
“…Following activation, the ABL kinases often promote phosphorylation of the activating RTK and engage in bidirectional signaling that may result in decreased internalization of the receptor (41). Activation of ABL kinases in KRAS-mutant-expressing cells may also be mediated by RTK signaling, as mutant KRAS promotes expression of the EGFR ligand epiregulin, which binds to wild-type EGFR in these cells, thereby promoting autocrine cell growth and survival (42). Thus, activation of ABL kinases in lung cancer cells with EGFR or KRAS mutations can occur independently of ABL genomic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Following activation, the ABL kinases often promote phosphorylation of the activating RTK and engage in bidirectional signaling that may result in decreased internalization of the receptor (41). Activation of ABL kinases in KRAS-mutant-expressing cells may also be mediated by RTK signaling, as mutant KRAS promotes expression of the EGFR ligand epiregulin, which binds to wild-type EGFR in these cells, thereby promoting autocrine cell growth and survival (42). Thus, activation of ABL kinases in lung cancer cells with EGFR or KRAS mutations can occur independently of ABL genomic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In the mice, increased expressions of Ereg mRNA have been reported in lung tumors induced by vinyl carbamate (Alyaqoub et al, 2008) or UR (Bauer et al, 2011). Increased expression of Ereg has also been reported in lung tumors of Tg mice that express the K-ras proto-oncogene (Sunaga et al, 2013). According to one study, mutations of the endogenous c-K-ras gene may not be the principal genetic events in UR-induced lung proliferative lesions in the rasH2 Tg mice (Mori et al, 2000), although mutations in the exogenous c-Ha-ras transgene are reported to play a pivotal role in the lung carcinogenesis (Tomisawa et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…This result may be due to H1395 cells possessing the greatest number of risk factors, as they were obtained from a female smoker with BRAF mutation (14)(15)(16)(17)(18). Comparison between each TADC-CM and mdDC-CM indicated that HCC2935-TADC-CM had the most marked effect on the proliferation, migration and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated the association between certain factors and the effect of BaP on lung cancer progression. Table I shows the background of the cell lines used in the present study (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). A previous study using CD-1 mice indicated that female mice are more susceptible to the carcinogenic effects of BaP compared with males (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation